Analisis Pengaruh Diferensiasi Produk, Diskon Harga, Dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan Reshare Rabbani Sumenep - Fadlilatul Khairiyah; Rois Arifin; M Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The study aims to know and analyze the impact of product differentiation, discounts prices, and services on the loyalty of Rabbani Sumenep Reshare customers. The study used case studies on Rabbani Sumenep's Reshare customers where the data was obtained by distributing the questionnaire to Rabbani sumenep's reshare using a sampling method. The population in this study is not definitely known as the number, so it uses the formula of hair et.al that obtained the number of samples as much as 95 respondents. The method of analysis used is the linear, linear regression analysis. The research shows that simultaneous or together dissociative variables of product, discount prices, and quality services affect customer loyalty and are partial deferment variables of product dissociation, discount prices, and service quality also have an effect on customer loyalty. Key words: customer loyalty, product deferation, price discount, quality of service